The The Influence Of Work Discipline And Organizational Commitment On Employee Performance At PT Nawakara Arta Kencana: Work Discipline, Organizational Commitment, Performance - Hendri Dunan; M Fitra Iryanto (International Journal of Economics, Business and Innovation Research, 2024)
This research explains the influence of work discipline and organizational commitment on employee performance at PT Nawakara Arta Kencana. The method used in this research is a case study of PT Nawakara Arta Kencana employees. Questionnaires were given to 30 employees from management level to staff level as respondents. The data analysis technique used is Multiple Linear Regression Analysis. The research results show that work discipline has a significant effect on employee performance, and organizational commitment has a significant effect on employee performance. Work discipline and organizational commitment simultaneously influence employee performance.